Evaluation of grass mixtures of a lawn type in the conditions of forest-steppe of the Middle Volga region - O. A. Timoshkin; O. Yu. Timoshkina; E. V. Timoshchuk (Аграрная наука Евро-Северо-Востока, 2021)
In 2019-2020, the quality of lawn-type grass mixtures based on creeping clover (Trifolium repens L.), meadow fescue (Festuca pratensis), pasture ryegrass (Lolium perenne) and meadow bluegrass (Poa pratensis) was evaluated in the conditions of the forest-steppe of the Middle Volga region (Penza region). The studied factors are the composition of the mixtures (creeping clover + bluegrass component), the seeding rates of the components (40 + 70 %; 55 + 55 %; 70 + 40 %) and the background of mineral nutrition (without fertilizers, P45K45, N30P45K45). The growing season during the years of research was characterized by arid conditions, the hydrothermal coefficient (HTC) for the period May-September in 2019 was 0.79, in 2020 - 0.76. On average, over two years of grass mixtures of creeping clover with meadow bluegrass at a seeding rate of 40 + 70 % and 70 + 40 % (from the seeding rate in pure form), creeping clover with meadow fescue with a seeding rate of 70 + 40 % components at all doses of mineral fertilizers had the highest comprehensive assessment of the quality of the lawn. The grass mixtures of creeping clover with meadow bluegrass (70 + 40 %) and creeping clover with meadow fescue (70 + 40 %) against the background of application of N30P45K45 had the maximum indicators in terms of herbage density (1425 and 1475 pcs/m2), which significantly exceeded the control and the variant with the introduction of Р45К45. In these variants, the highest indicators of projective cover (97.5 %) and a comprehensive assessment of "excellent" and "highest quality". According to weediness, the crops were estimated at 1 point (slightly weedy), per 1 m2 of annual and biennial weeds there were 24-27 pcs., rhizome weeds - less than 10 pcs. per 1 m2, the area of weed projective cover did not exceed 5 %.